Combined effect of heat and nutritional stress on superovulation of Malpura ewes in a semi-arid region. (February 2019) - Kumar, Davendra; De, Kalyan; Shekhawat, Indu; Bahadur, Saumya; Balaganur, Krishnappa; Naqvi, S.M.K.
Abstract: Sheep reared in hot semi-arid environments are generally exposed to heat and nutritional stress in some seasons of the year, which affects both production and reproduction. To assess the effect of high ambient temperature and feed scarcity on superovulation, 16 adult Malpura ewes were randomly divided into two groups of 8 animals each. G1 (control) was kept under a shed and offered a maintenance diet, and G2 (combined stress) was subjected to both nutritional (30% less of maintenance diet) and heat (38–44 °C for 6 h/day) stress. Ewes were superovulated without estrus synchronization by a combination of single injection of 200 IU eCG and 8 injections of FSH (Folltropin-V) at 12-h intervals in tapering doses of 5 mg/kg body weight, starting from the day 7 of natural estrus. eCG was given with the first injection and PGF2α (10 mg) was given with the second last FSH injection. G2 increased respiration rate and rectal temperature (P < 0.01), and blood urea level (P < 0.05), whereas it decreased average daily gain, plasma T4 concentration (P < 0.01) and body weight (P < 0.05). Plasma estradiol level was lower (P < 0.05) in G2 ewes as compared to control (G1) ewes. However, the number of ewes showed a superovulatory response (88 vs 66% ewes ≥ 3 corpus luteum), ovulation rate (8.75 vs 5.88) and embryo production (5.5 vs 3.9) decreased, and the number of large follicles (anovulation) increased (1.0 vs 2.14) in G2 ewes. G2 had a comparable effect on the superovulatory response compared to control ewes although physiological changes occurred as an adaptive mechanism to stress. Therefore, the well-adapted cyclic sheep of the semi-arid region may be used for superovulation despite the stressful condition of heat exposure and nutritional insufficiency. Highlights: The combined effect of nutritional and heat stress drastically decrease feed intake in Malpura ewes. Combined heat and nutritional stress affects Malpura physiology. Plasma estradiol, progesterone and T4 in Malpura sheep are modified with nutritional and heat stress. Malpura sheep can respond to superovulation in semi-arid regions despite nutritional and heat stress.